Anatomy of the medical image : knowledge production and transfiguration from the renaissance to today - Fliethmann, Axel; Weller, Christiane, 1962- (Clio medica (Amsterdam, Netherlands) ;, 2021)
"This volume addresses the interdependencies between visual technologies and epistemology with regard to our perception of the medical body. It explores the relationships between the imagination, the body, and concrete forms of visual representations: Ranging from the Renaissance paradigm of anatomy, to Foucault's "birth of the clinic" and the institutionalised construction of a "medical gaze"; from "visual" archives of madness, psychiatric art collections, the politicisation and economisation of the body, to the post-human in mass media representations. Contributions to this volume investigate medical bodies as historical, technological, and political constructs, constituted where knowledge formation and visual cultures intersect. Contributors are: Axel Fliethmann, Michael Hau, Birgit Lang, Carolyn Lau, Heikki Lempa, Stefanie Lenk, Joanna Madloch, Barry Murnane, Jill Redner, Claudia Stein, Elizabeth Stephens, Corinna Wagner, and Christiane Weller"--